Characterization of phonon thermal transport of Ti3C2Tx MXene thin film. (13th April 2022) - Wu, Hao; Gu, Jiaxin; Li, Zhongcheng; Liu, Wenxiang; Bao, Hua; Lin, Huan; Yue, Yanan
Abstract: Two-dimensional MXene materials with high electrotonic conductivity, good chemical stability, and unique laminar structure show great potential in the field of electrochemistry. In contrast to the widely concerned electrical properties, studies on the thermal properties of MXene materials are very limited. This paper presents a comprehensive analysis of the thermal properties of Ti3 C2 T x MXene thin film. Thermal diffusivity and thermal conductivity of Ti3 C2 T x films are characterized by the transient electro-thermal technique. The experimental results show a 16% enhancement in thermal conductivity when the temperature is increased from 307 K to 352 K. The phonon transport contributes substantially to thermal conductivity compared with electron transport. Molecular dynamic simulation is employed to further investigate the role of phonon thermal transport of Ti3 C2 layer. It is found that the combined effect of specific heat capacity, stacking structure and internal stress states is responsible for the thermal transport performance of Ti3 C2 T x MXene thin film.